Focal calcium monitoring with targeted nanosensors at the cytosolic side of endoplasmic reticulum. Issue 1 (1st December 2016) - Hou, Yanyan; Arai, Satoshi; Takei, Yoshiaki; Murata, Atsushi; Takeoka, Shinji; Suzuki, Madoka
Abstract: Ca 2+ distribution is spatially and temporally non-uniform inside cells due to cellular compartmentalization. However, Ca 2+ sensing with small organic dyes, such as fura-2 and fluo-4, has been practically applied at a single cell level where the averaged signal from freely diffusing dye molecules is acquired. In this study, we aimed to target azide-functionalized fura-2 (N3 -fura-2) to a specific site of subcellular compartments to realize focal Ca 2+ sensing. Using scAVD (single-chain avidin)–biotin interaction and a copper-free click reaction system, we linked N3 -fura-2 to specifically-targeted scAVD protein fused with a red fluorescent protein mCherry, so that Ca 2+ sensors conjugated with four N3 -fura-2 dyes with dibenzocyclooctyne (DBCO)-PEG4-biotin as a linker were generated at subcellular compartments in living cells. In cytoplasm, N3 -fura-2 showed a prolonged retention period after binding to scAVD. Furthermore, the reacted N3 -fura-2 was retained inside cells even after free dyes were washed out by methanol fixation. When scAVD was overexpressed on endoplasmic reticulum (ER) membranes, N3 -fura-2 was accumulated on ER membranes. Upon histamine stimulation, which increases cytosolic Ca 2+ concentration, ER-localized N3 -fura-2 successfully sensed the Ca 2+ level changes at the cytosolic side of ER membrane. Our study demonstrated specific targeting of N3 -fura-2 to subcellular compartments and the ability of sensing focal Ca 2+ level changes with the specifically targeted Ca 2+ sensors. Abstract :